Electromagnetics and Network Theory and their Microwave Technology Applications A Tribute to Peter Russer - Lindenmeier, Stefan; Weigel, Robert; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg Imprint: Springer, 2011)
This book gives a compact overview about actual research in the field of Electromagnetics and Network Theory and its Microwave Applications. It contains aspects on antennas and wave propagation, microwave- and communication-systems and methods for the numerical modeling of components, networks and structures being part of these systems. An actual state of research in antennas and propagation is given as well as wave propagation in RF-lines and electric networks which are crucial for the investigation of microwave systems like radar-, radio-location- and communication- systems. Especially in mobile applications, radar- , radio-location- and navigation- systems as well as microwave sensors are more and more in use. Therefore an actual state of research in this field is given. Actual results of research on such systems are shown for automotive radar, a high precision radio-location-system, RF-sensors and RF-measurement technologies. The wide field of communication systems is further discussed where an overview about progress in mobile communication and wireless data transmission is given and results of actual research are shown. At last, actual numerical methods are discussed which are essential for the estimation of electromagnetic effects in all the applications shown previously. In the scope between the treatment of very tiny structures and very large structures new ways are shown for the numerical modeling of the electromagnetic field in nanostructures as well as in macrostructures and large periodic structures. The book is dedicated to Prof. Dr. Dr. hc. Peter Russer and his research work which is shown in his autobiography.
Antennas and Propagation -- A Hybrid MoM/UTD Method for the Analysis of a Monopole Antenna in an Aperture -- Electromagnetic and Network Theory of Waveguide Radiation by Spherical Modes Expansions -- Circuit Representation and Performance Analysis of Phased Array Antennas Including Mutual Coupling Effects -- Time-Domain Modelling of Group-Delay and Amplitude Characteristics in Ultra-Wideband Printed-Circuit Antennas -- Time-Domain Modelling of Group-Delay and Amplitude Characteristics in Ultra-Wideband Printed-Circuit Antennas -- Diffraction of Acoustic and Electromagnetic Waves by Impedance Cones -- Microwave Systems -- Pattern Design and DBF Analysis of a Dielectric Lens Antenna for 77GHz Automotive Long Range Radar -- High precision distance measurement for pedestrian protection using cooperative sensors -- A High-Precision Wideband Local Positioning System at 24 GHz -- Monitoring of Electrochemical Processes in Catalysts by Microwave Methods -- Communication Technology -- Mobile Phones: The Driving Force towards the Integration of Analog and Digital Blocks for Baseband and RF Circuitry -- Wireless for Industrial Automation - Significant Trend or Overrated? -- Sub-Microsecond Contactless Ultra-Wideband Data Transmission in Rotating Systems Using a Slotted Waveguide Ring -- Green Inkjet-Printed Wireless Sensor Nodes on Low-Cost Paper, Liquid and Flexible Organic Substrates -- A Joint Matlab/FPGA Design of AM Receiver for Teaching Purposes -- MoM based EMI Analysis on Large Wind Turbine GSM Communication System -- Numerical Methods for Electromagnetic Field Modeling -- Novel Frequency- and Time-Domain Techniques for the combined Maxwell- Dirac Problem in the Characterization of Nanodevices -- Electromagnetic Partitioning Methodology towards Multi-Physics Chip-Package-Board Co-design and Co-Simulation -- Parallel TLM Procedures for NVIDIA GPU -- Stability Enhancement of Digital Predistortion through Stationary Iterative Methods to Solve System of Equations -- Analysis of complex periodic structures -- Macromodeling in Finite Differences -- Autobiography -- The Impossible Takes Longer.
Keywords: Electronic books; Engineering; Computer science; Microwaves; Microwaves, RF and Optical Engineering; Optics and Electrodynamics; Computational Science and Engineering